Superior 2-Year Functional Outcomes Among Young Female Athletes After ACL Reconstruction in Just 10 Post-Operative Return-to-Sport Training Sessions. Issue 7 (29th July 2019) - Capin, Jacob John; Failla, Mathew; Smith, Angela H.; Zarzycki, Ryan; Dix, Celeste; Johnson, Jessica Lindsey; Risberg, May Arna; Huston, Laura J.; Spindler, Kurt P.; Snyder-Mackler, Lynn
Objectives: Outcomes after anterior cruciate ligament reconstruction (ACLR) are not uniformly acceptable and are worse among young female athletes. Developing better rehabilitation and return-to-sport (RTS) training programs and evaluating their outcomes are essential. The purposes of this study were to: 1) Test the effect of strength, agility, plyometric, and secondary prevention (SAPP) exercises with and without perturbation training (SAPP+PERT) on strength, hops, functional outcomes, activity levels, and RTS rates in young female athletes 1 and 2 years after ACLR; and 2) Compare 2-year functional outcomes and activity levels among young female athletes in the ACL-SPORTS trial to homogeneous cohorts who completed criterion-based post-operative rehabilitation alone (MOON) and in combination with extended pre-operative rehabilitation (DE-Oslo). We hypothesized that SAPP+PERT would result in superior outcomes compared to SAPP alone; and female athletes who structured completed post-operative RTS training, compared to those who did not, would have higher functional outcomes. Methods: Aim 1 is a randomized control trial (NCT01773317) while aim 2 is a cohort study. For aim 1, we enrolled 39 female athletes, based on power calculations described previously. Athletes were enrolled 3-9 months after primary ACLR when they achieved impairment resolution. Participants were randomized to 10 SAPP or SAPP+PERT sessions (˜2x/week) and tested 1 and 2 years after ACLR on quadriceps strength, 4 hop tests, functional outcome measures, and RTS rates. We used 2x2 mixed-model ANOVA to test aim 1 (α = 0.05). Secondary to no group differences, we collapsed across SAPP and SAPP+PERT for aim 2. We applied inclusion/exclusion criteria and constrained sex (female) and age (13 to < 25 years) to compare these athletes who received post-operative RTS training (ACL-SPORTS) to homogeneous subsets who completed criterion-based post-operative rehabilitation alone (MOON) and combined with extended pre-operative rehabilitation (DE-Oslo) on 2-yr outcomes: the International Knee Documentation Committee Subjective Knee Evaluation Form (IKDC), Knee Injury and Osteoarthritis Outcome Score (KOOS), and Marx Activity Rating Scale. We tested aim 2 using 3-way ANOVA and Chi-Square test of proportions to compare the proportion of individuals in each group who met the Patient Acceptable Symptom State (PASS) thresholds. Results: There were no significant or clinically meaningful differences between SAPP and SAPP+PERT; groups were collapsed for comparison to the other cohorts. ACL-SPORTS had the highest scores on every outcome (Table 1). A higher proportion of ACL-SPORTS achieved the PASS thresholds for the IKDC, KOOS Activities of Daily Living, and KOOS Sport and Recreation (Fig 1, p ≤ .01). Conclusion: Our 1st hypothesis, that the addition of perturbation training would result in superior clinical and functional outcomes, was not supported. Our 2nd hypothesis, that a structured RTS training program would improve outcomes over existing cohorts, was supported. Post-operative RTS training incorporating strengthening, agilities, and plyometrics but not necessarily perturbation training, may improve functional outcomes and activity levels among young female athletes after ACLR. We provide a prototype for RTS training that would be feasible to implement into group or non-clinical environments. Future RCTs should assess the comparative effectiveness of RTS training in various settings. Table 1. All 2-year functional outcome measures differed across groups. Values are mean (SD). Outcome Variables MOON DE-Oslo ACL-SPORTS P-Value Marx 10.6 (5.1) 12.5 (2.7) 13.5 (3.3) 0.008 IKDC 83.6 (13.9) 91.7 (8.6) 95.9 (6.8) <0.001 KOOS Pain 90.4 (10.3) 94.4 (9.4) 97.9 (3.9) <0.001 KOOS Symptoms 83.4 (14) 89.6 (9.4) 93.5 (6.3) <0.001 KOOS Activities of Daily Living 95.7 (7.1) 98.8 (4.2) 99.8 (0.5) 0.002 KOOS Sport and Recreation 81.6 (17.1) 86.0 (15.4) 94.4 (7.6) 0.001 KOOS Knee Related Quality of Life 76.3 (18.7) 78.3 (17.6) 89.1 (13.9) 0.004 Fig 1a. Proportion Who Met IKDC PASS Threshold Fig 1b. Proportion Who Met KOOS ADL PASS Threshold Fig 1c. Proportion Who Met KOOS Sport/Rec PASS Threshold